2004
DOI: 10.1085/jgp.200409030
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Role of H+ in Chemotactic Signaling of Sperm

Abstract: Chemotaxis of sperm is an important step toward fertilization. During chemotaxis, sperm change their swimming behavior in a gradient of the chemoattractant that is released by the eggs, and finally sperm accumulate near the eggs. A well established model to study chemotaxis is the sea urchin Arbacia punctulata. Resact, the chemoattractant of Arbacia, is a peptide that binds to a receptor guanylyl cyclase. The signaling pathway underlying chemotaxis is still poorly understood. Stimulation of sperm with resact i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 43 publications
0
36
1
Order By: Relevance
“…In this regard, our group found that speract from pM to nM concentrations increases pHi before [Ca 2+ ]i in S. purpuratus sperm populations [12,13]. Although earlier sperm population studies in Arbacia punctulata concluded that pM resact (the corresponding chemoattractant peptide) first elevates [Ca 2+ ]i and then pHi, and that this alkalinization did not influence chemotaxis [14], recently the authors of this study reported that alkalinization precedes the [Ca 2+ ]i elevation, and importantly, that it presumably stimulates…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In this regard, our group found that speract from pM to nM concentrations increases pHi before [Ca 2+ ]i in S. purpuratus sperm populations [12,13]. Although earlier sperm population studies in Arbacia punctulata concluded that pM resact (the corresponding chemoattractant peptide) first elevates [Ca 2+ ]i and then pHi, and that this alkalinization did not influence chemotaxis [14], recently the authors of this study reported that alkalinization precedes the [Ca 2+ ]i elevation, and importantly, that it presumably stimulates…”
Section: Introductionmentioning
confidence: 79%
“…This intracellular alkalinization was proposed to mediate peptide receptor and guanylate cyclase inactivation through dephosphorylation [21,[23][24][25], though recent results question this proposal [26]. Sea urchin sperm population experiments had yielded contradictory results regarding their pHi responses to egg peptides [12][13][14]. Recent agreement regarding the kinetic precedence of pHi over [Ca 2+ ]i lead Seifert et al [6] to propose that the resact-induced pHi increase activates CatSper, the flagellar sperm specific pHi-activated Ca 2+ channel, regulating A. punctulata sperm chemotaxis.…”
Section: Discussionmentioning
confidence: 99%
“…The Kaupp group has reported that in A. punctulata and S. purpuratus the pHi increase at low SAP concentrations occurs after, not before, the [Ca 2+ ]i elevation and that the intracellular alkalinization is not due to activation of Na + /H + exchange induced by the hyperpolarization but probably caused by cytosolic proton consumption during GTP and ATP replenishment (Kaupp et al, 2006;Solzin et al, 2004;Strunker et al, 2006). These results are in conflict with those obtained by Nishigaki et al (2001Nishigaki et al ( , 2004.…”
Section: B Amentioning
confidence: 91%
“…Like resact, speract activates a cGMP-signaling pathway (Cook and Babcock 1993;Matsumoto et al 2003;Solzin et al 2004). However, the speract receptor, a 77 kDa plasma membrane receptor localized exclusively in the sperm flagellum, has been reported to be unrelated to guanylyl cyclase (Dangott et al 1989;Cardullo et al 1994).…”
Section: Cross-talk Between Gametesmentioning
confidence: 99%
“…However, the speract receptor, a 77 kDa plasma membrane receptor localized exclusively in the sperm flagellum, has been reported to be unrelated to guanylyl cyclase (Dangott et al 1989;Cardullo et al 1994). The speract-induced motility changes in S. purpuratus sperm closely resemble those of other marine species whose sperm undergo chemotaxis, but attempts have failed to demonstrate its chemotactic activity (Solzin et al 2004;Wood et al 2007). It was suggested that resact, speract and other SAPs function through a common signal transduction pathway to stimulate and orient sperm motility, and that this signal involves changes in intracellular pH, in the concentrations of cGMP, cAMP as well as Na + and Ca 2+ ions, in membrane potential and in the phosphorylation pattern of several proteins (Ward and Kopf 1993;Cook et al 1994;Darszon et al 2005Darszon et al , 2006Wood et al 2007).…”
Section: Cross-talk Between Gametesmentioning
confidence: 99%